Developing Android Applications with Flex 4.5 - Tretola, Rich (O'Reilly Media, 2012)
Ready to put your ActionScript 3 skills to work on mobile apps? This hands-on book walks you through the process of creating an Adobe AIR application from start to finish, using the Flex 4.5 framework.